Distinct roles for interleukin-23 receptor signaling in regulatory T cells in sporadic and inflammation-associated carcinogenesis - Jacobse, Justin; Pilat, Jennifer M.; Li, Jing; Brown, Rachel E.; Kwag, Aaron; Buendia, Matthew A.; Choksi, Yash A.; Washington, M. Kay; Williams, Christopher S.; Markham, Nicholas O.; Short, Sarah P.; Goettel, Jeremy A. (Frontiers in Oncology, 2024)
Introduction The pro-inflammatory cytokine interleukin-23 (IL-23) has been implicated in colorectal cancer (CRC). Yet, the cell-specific contributions of IL-23 receptor (IL-23R) signaling in CRC remain unknown. One of the cell types that highly expresses IL-23R are colonic regulatory T cells (Treg cells). The aim of this study was to define the contribution of Treg cell-specific IL-23R signaling in sporadic and inflammation-associated CRC. Methods In mice, the role of IL-23R in Treg cells in colitis-associated cancer (CAC) was investigated using azoxymethane/dextran sodium sulphate in wild-type Treg cell reporter mice (WT, Foxp3YFP-iCre), and mice harboring a Treg cell-specific deletion of IL-23 (Il23rΔTreg). The role of IL-23R signaling in Treg cells in sporadic CRC was examined utilizing orthotopic injection of the syngeneic colon cancer cell line MC-38 submucosally into the colon/rectum of mice. The function of macrophages was studied using clodronate. Finally, single-cell RNA-seq of a previously published dataset in human sporadic cancer was reanalyzed to corroborate these findings. Results In CAC, Il23rΔTreg mice had increased tumor size and increased dysplasia compared to WT mice that was associated with decreased tumor-infiltrating macrophages. In the sporadic cancer model, Il23rΔTreg mice had increased survival and decreased tumor size compared to WT mice. Additionally, MC-38 tumors of Il23rΔTreg mice exhibited a higher frequency of pro-inflammatory macrophages and IL-17 producing CD4+ T cells. The decreased tumor size in Il23rΔTreg mice was macrophage-dependent. These data suggest that loss of IL-23R signaling in Treg cells permits IL-17 production by CD4+ T cells that in turn promotes pro-inflammatory macrophages to clear tumors. Finally, analysis of TCGA data and single-cell RNA-seq analysis of a previously published dataset in human sporadic cancer, revealed that IL23R was highly expressed in CRC compared to other cancers and specifically in tumor-associated Treg cells. Conclusion Inflammation in colorectal carcinogenesis differs with respect to the contribution of IL-23R signaling in regulatory T cells.